PROSPEK PENGEMBANGAN UMKM PENGOLAHAN IKAN DI KOTA AMBON - Stevanus Marelly Siahainenia; Johanis Hiariey (Universitas Pattimura, 2017)
Small- and medium Micro Enterprises (SMME) of fish processing in Ambon City play an important role in employment and income, but identified that the enterprises deal with developing problems. The objectives of this research are to identify characteristics of the micro enterprises of fish processing, to analyze financial feasibility, and to identify determinant of development of the micro enterprises of fish processing in Ambon city. Primary data were gathered from six micro enterprise units of fish processing using survey technique, while secondary data were obtained from official publications. Data were analyzed using qualitative and quantitative methods. The results show that the micro enterprises of the fish processing are categorized as a small- and medium enterprise (SMME) based on the business capital, level of production, ineffectual function of institution, locally product marketing, and lack of management skill in business. Empirical results indicate the SMME of CV. Nacha and PT. Maluku Maya Mandiri are feasible to be developed. Some factors that need to be concerned in developing the SMME of fish processing in Ambon city are of capital availability, skilled worker, product promotion, and marketing strategy.